2016
DOI: 10.2337/dc16-0269
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations of Exposure to Perfluoroalkylated Substances in Childhood and Adolescence and Indicators of Adiposity and Glucose Metabolism 6 and 12 Years Later: The European Youth Heart Study

Abstract: OBJECTIVETo investigate the long-term association of exposure to perfluoroalkylated substances, including perfluorooctanesulfonic acid (PFOS) and perfluorooctanoic acid (PFOA), during childhood (9 years) and adolescence (15 years) on indicators of adiposity and glucose metabolism in adolescence (15 years) and young adulthood (21 years). Secondarily, we aim to clarify the degree of tracking of exposure from childhood into young adulthood. RESEARCH DESIGN AND METHODSData derived from a large multicenter prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 29 publications
(35 reference statements)
4
80
2
1
Order By: Relevance
“…Previous studies have suggested prenatal PFAS concentrations to be related with BMI (34,35). As such, BMI may arguably be considered an intermediate factor on the causal pathway between PFAS and glycemic status.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have suggested prenatal PFAS concentrations to be related with BMI (34,35). As such, BMI may arguably be considered an intermediate factor on the causal pathway between PFAS and glycemic status.…”
Section: Discussionmentioning
confidence: 98%
“…Several human cohort studies have shown that higher levels of prenatal or early-life PFOA exposure is associated with increased adiposity in childhood (Braun et al 2016;Fleisch et al 2017) and metabolic disruption in young adulthood (Domazet et al 2016). Additionally, it is known that low birth weight is associated with adult diseases, including metabolic syndrome in both humans and animals (Barker 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the causes of weight change are likely heterogeneous (including diet, physical activity, and medications) and often not well understood in observational studies. Prospective evidence linking PFAS exposure with body weight regulation was primarily from studies that examined prenatal or early life exposures to PFASs in relation to body weight later in life, and the results were somewhat mixed [ 21 27 , 48 , 49 ]. For example, in 3 birth cohort studies conducted in European populations, maternal concentrations of PFASs were significantly associated with offspring body weight and other anthropometric and metabolic traits, primarily among girls [ 21 , 23 , 25 ].…”
Section: Discussionmentioning
confidence: 99%